Impacts of Use and Abuse of Nature in Catalonia with Proposals for Sustainable Management - Josep Peñuelas; Josep Germain; Enrique Álvarez; Enric Aparicio; Pere Arús; Corina Basnou; Cèsar Blanché; Núria Bonada; Puri Canals; Marco Capodiferro; Xavier Carceller; Alexandre Casademunt; et al. (Land, 2021)
This paper provides an overview of the last 40 years of use, and in many cases abuse, of the natural resources in Catalonia, a country that is representative of European countries in general, and especially those in the Mediterranean region. It analyses the use of natural resources made by mining, agriculture, livestock, logging, fishing, nature tourism, and energy production and consumption. This use results in an ecological footprint, i.e., the productive land and sea surface required to generate the consumed resources and absorb the resulting waste, which is about seven times the amount available, a very high number but very similar to other European countries. This overexploitation of natural resources has a huge impact on land and its different forms of cover, air, and water. For the last 25 years, forests and urban areas have each gained almost 3% more of the territory at the expense of agricultural land; those municipalities bordering the sea have increased their number of inhabitants and activity, and although they only occupy 6.7% of the total surface area, they account for 43.3% of the population; air quality has stabilized since the turn of the century, and there has been some improvement in the state of aquatic ecosystems, but still only 36% are in good condition, while the remainder have suffered morphological changes and different forms of nonpoint source pollution; meanwhile the biodiversity of flora and fauna remains still under threat. Environmental policies do not go far enough so there is a need for revision of the legislation related to environmental impact and the protection of natural areas, flora, and fauna. The promotion of environmental research must be accompanied by environmental education to foster a society which is more knowledgeable, has more control and influence over the decisions that deeply affect it. Indeed, nature conservation goes hand in hand with other social and economic challenges that require a more sustainable vision. Today’s problems with nature derive from the current economic model, which is environmentally unsustainable in that it does not take into account environmental impacts. Lastly, we propose a series of reasonable and feasible priority measures and actions related to each use made of the country’s natural resources, to the impacts they have had, and to their management, in the hope that these can contribute to improving the conservation and management of the environment and biodiversity and move towards sustainability.